Tailoring the Functional Potential of Red Beet Purées by Inoculation with Lactic Acid Bacteria and Drying - Gabriel-Dănuț Mocanu; Ana Cosmina Chirilă; Aida Mihaela Vasile; Doina Georgeta Andronoiu; Oana-Viorela Nistor; Vasilica Barbu; Nicoleta Stănciuc (Foods, 2020)
This study was focused on a comparative analysis of two drying methods, such as convective and infrared drying, on the red beetroot purées with lactic acid bacteria, as a strategy for tailoring the health benefits of the selected plant. For both varieties, the total betalain contents varied from 13.95 ± 0.14 mg/g dry weight in Beta vulgaris var. cylindra when compared with 11.09 ± 0.03 mg/g dry weight in Beta vulgaris var. vulgaris, whereas significant differences were found in total phenolic and flavonoid contents. Significant drying induced changes were found in selected bioactives, in terms of total betalains, flavonoids, and polyphenols, which influenced the antioxidant activities of the purées, structure, and color parameters. In general, infrared technology was more protective, leading to an increase of 20% in flavonoids content. One logarithmic decrease in cell viability was observed in all powders samples. After the in vitro digestion, the betalains decreased, in both gastric and intestinal simulated juices, with a more pronounced profile in infrared processed purées. Textural and rheological analysis of the dried purées highlighted that the infrared drying is milder compared to the conventional one, allowing us to obtain powders with enhanced functional properties, in terms of bioactives content, cell viability, color, and structural and rheological behavior.